Culture, Location, and Establishment Modes in Foreign Direct Investment: National and Regional Level Analysis - Carlson, Joshua (My University, 2014)
Culture has become an important topic as firms expand operations around the globe, while at the same time as distance becomes shorter and technology advances. In the same way that Foreign Direct Investment (FDI) has become an ever increasing aspect of business as the world becomes smaller. The basis of the research is to gain understanding on the effects of culture at the regional levels in regards to FDI and the establishment mode of choice. The study aims to builds on past research especially in the area of regional level by examine the differences between national and regional culture. The study used a quantitative approach to examine Finnish firms FDI transactions at the National and Regional level from 1995-2010. The National level examined 22 countries, and the total observations equaled 1000. The Regional level aspect of the study examined the Finnish firms FDI transactions for 11 countries in Europe at the regional level (NUTS1) and the total FDI observations totaled 569 from 162 different firms. The key components of the analysis were cultural distance, cultural dimensions, regional GDP, FDI attractiveness, and establishment modes. The general findings from the research found that the role of regional culture and economy had an effect on location selection for Finnish firms FDI. The regional level results found Finnish firms prefer to undertake FDI in countries which were closer in terms of cultural distance. Also, acquisitions were the preferred establishment mode at the regional and national level, especially in locations which are closer in terms of cultural distance. The results implied that regional level cultural distance along with regional level GDP could provide be beneficial in the FDI location selection process, especially for Finnish firms.
Keywords: Regional Level Culture; Foreign Direct Investment; Establishment Modes; Location; FDI Attractiveness; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|